2019
DOI: 10.1111/aas.13354
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐acquired complications in intensive care unit patients with diabetes: A before‐and‐after study of a conventional versus liberal glucose control protocol

Abstract: BackgroundCritically ill patients with diabetes mellitus (DM) are at increased risk of in-hospital complications and the optimal glycemic target for such patients remains unclear. A more liberal approach to glucose control has recently been suggested for patients with DM, but uncertainty remains regarding its impact on complications. MethodsWe aimed to test the hypothesis that complications would be more common with a liberal glycemic target in ICU patients with DM. Thus, we compared hospital-acquired complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, diabetic subgroup with the HbA1c ≥ 6.5% was not associated with hypoglycemia, unlike the non-diabetic and pre-diabetic subgroups in the present study. Previous studies demonstrated that liberal glucose control reduced hypoglycemia in critically ill patients with HbA1c ≥ 7% [22,23]. Thus, even if the association between hypoglycemia and unfavorable neurologic outcome is unclear in the present study, it might be acceptable to recommend the EAG based glucose control in cardiac arrest survivors with chronic hyperglycemic status to avoid potential harm owing to hypoglycemia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, diabetic subgroup with the HbA1c ≥ 6.5% was not associated with hypoglycemia, unlike the non-diabetic and pre-diabetic subgroups in the present study. Previous studies demonstrated that liberal glucose control reduced hypoglycemia in critically ill patients with HbA1c ≥ 7% [22,23]. Thus, even if the association between hypoglycemia and unfavorable neurologic outcome is unclear in the present study, it might be acceptable to recommend the EAG based glucose control in cardiac arrest survivors with chronic hyperglycemic status to avoid potential harm owing to hypoglycemia.…”
Section: Discussionmentioning
confidence: 74%
“…Although the multivariate models and propensity-score matched cohort failed to show any significant association between the glucose group and neurologic outcome, the final model adjusted for the interaction of HbA1c and mean glucose showed that the association between hyperglycemia and the neurologic outcome might differ according to the premorbid glycemic status. Previous studies demonstrated that liberal (180–252 mg/dL) glucose control was not associated with increased mortality or adverse events, whereas liberal glucose control was associated with reduced hypoglycemia and glucose variability than conventional (108–180 mg/dL) glucose control in critically ill patients with diabetes or patients with chronic hyperglycemia (HbA1c ≥ 7%) [21,22,23]. That previous research supports that HbA1c based glucose control might be better to avoid potential risk of adverse events in cardiac arrest survivors with chronic hyperglycemia or poorly controlled diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with insufficiently controlled diabetes (HbA1c ≥7%) the incidence of hypoglycaemia was reduced with the liberal regimen without adversely affecting the duration of mechanical ventilation or mortality [21]. In subsequent analyses, liberal glucose control was not associated with an increased risk of hospital-acquired infections, cardiovascular, renal or neurological complications [22 ▪ ]. There are substantial limitations to both studies including that the intervention was not blinded, patients were not randomised and the before-and-after and historical comparator designs increase the risk of seasonal and secular changes introducing bias but these studies suggest that hypoglycaemia, a biomarker of harm, may be reduced with such an approach.…”
Section: Increasing Glycaemic Targets For Patients With Type 2 Diabet...mentioning
confidence: 93%
“…The prospective studies evaluating a more liberal approach to glucose targets in patients with diabetes are limited to single-center studies that each have substantial methodological weaknesses [29 ▪ ,30,31]. Nonetheless, the signal from these studies is that allowing modest hyperglycemia before commencing insulin and targeting blood glucose concentrations between 180 and 250 mg/dL (10 and 14 mmol/L) appears well-tolerated with a tendency to reduce episodes of hypoglycemia [29 ▪ ,30,31,32].…”
Section: Updates For Glucose Targetsmentioning
confidence: 99%